Screening, counseling and referral pattern of structural heart disease in pregnancy cases at public health center in Surabaya - Noorma Rina Hanifah; Andrianto Andrianto; Bambang Trijanto (Universitas Airlangga, 2017)
Objectives: To depict the process of screening, counseling and re-ferral patterns of structural heart disease in pregnancy cases by public health centre in Surabaya as preliminary data required for the groundwork of standard of care of pregnancy with heart di-sease.Materials and Methods: This is a qualitative research with in-depth interview to PJ KIA doctors selected by purposive sam-pling, the information is confirmed by the Head of Primary Service Management Unit of BPJS Surabaya branch, Family Health Unit staff of Surabaya Municipality Health Office and 8 patients with structural heart disease in pregnancy treated in RSUD Dr. SoetomoResults: The process of early pregnancy screening at the PHC is performed by midwives and GPs in accordance to the format provided by of the Surabaya Municipality Health Office which was not designed for structural heart disease screening in preg-nancy, history taking and special physical examination for scree-ning of heart disease only done if suspicion occurs. Medical and Child Health program overseer doctors have not agreed on which referral facility for pregnancy cases with suspicion of structural heart disease should be directed because there is no guiding regulation. Counseling of pregnant patients suspected of having structural heart disease is still limited to providing infor-mation that PHC are unable to make a diagnosis.Conclusion: The process of screening for structural heart disease during pregnancy has not been done routinely through anamnesis and physical examination. There is no standard guidance on the process of referral of pregnancy cases with suspicion of structural heart disease that can be performed by Mother and Child Health programs overseer doctors. Visits of women with structural heart disease to the PHC to obtain referral letter to secondary / tertiary health facilities and School Health Program programs have not been utilized for counseling on the effect of heart disease on reproductive health.